Impact of Traffic Congestion on Road Users in Tangerang City - Sekarsari, Meira; Dwiatmoko, Hermanto (ASTONJADRO, 2022)
One of the negative impacts of transportation problems is congestion. Traffic congestion in urban areas is gradually becoming an important social and economic problem that needs to be addressed. Tangerang City is one of the supporting cities for the Jakarta metropolitan area as well as an area with a significant increase in population and vehicles, resulting in an increase in the number of people's movements or mobility in order to meet the needs of life. Meanwhile, the length of roads in Tangerang City during 2018-2019 did not increase and it is possible that there will be an imbalance between movement and available road capacity or minimal accessibility. The research approach used is quantitative with primary data sources obtained from closed questionnaire instruments from 180 road user respondents at the TangCity Mall intersection, Tangerang City. Analysis of the data used is a structural equation model with the AMOS 22.00 program to determine the factors that influence the impact of congestion. The results of the analysis show that the factors that most influence the impact of congestion are decreased concentration and loss of energy during traffic jams, which are more common in men who are married at the age of over 35 years, with a diploma level of education, as well as the type of work as a Civil Servant.